Yes Africa can : success stories from a dynamic continent - Chuhan-Pole, Punam; Angwafo, Manka (Washington, D.C. : World Bank, 2011)
This volume, a product of the staff of the international Bank of Construction and Development, aims to address how subsaharan African countries have overcome major development challenges. The main components of each case study include a description of the achievement and the elements that qualify the as susccessful; an assessment of the of the main policies, interventions , actions and other factors that contributed to the positive outcome. , a presentation of the lessons learned and the to the discourse on African development and insights on the usability or applicability of the achievement in terms of the potential for scaling up the interventions and actios.
Includes bibliographical references.
opc 30/04/13
Loan
Keywords: Success stories; Economic transformation/growth; Governance; Agriculture/Human development; African can; Africa